On Fractional Orthonormal Polynomials of a Discrete Variable - I. Area; J. D. Djida; J. Losada; Juan J. Nieto (Discrete Dynamics in Nature and Society)
A fractional analogue of classical Gram or discrete Chebyshev polynomials is introduced. Basic properties as well as their relation with the fractional analogue of Legendre polynomials are presented.